How Commodity Price Curves and Inventories React to a Short-Run Scarcity Shock - Erbil, Nese (IMF Working Papers; Working Paper, 2010)
How does a commodity market adjust to a temporary scarcity shock which causes a shift in the slope of the futures price curve? We find long-run relationships between spot and futures prices, inventories and interest rates, which means that such shocks lead to an adjustment back towards a stable equilibrium. We find evidence that the adjustment is somewhat consistent with well-known theoretical models, such as Pindyck (2001); in other words, spot prices rise and then fall, while inventories are used to absorb the shock. Importantly, the pace and nature of the adjustment depends upon whether inventories were initially high or low, which introduces significant nonlinearities into the adjustment process.